2003
DOI: 10.1212/01.wnl.0000071229.11658.f8
|View full text |Cite
|
Sign up to set email alerts
|

Face imagery and its relation to perception and covert recognition in prosopagnosia

Abstract: Although anterior temporal cortex may be the site of facial memory stores, these data also support hypotheses that perceptual areas like the fusiform face area have parallel contributions to mental imagery. The data on covert recognition are consistent with a view that it is the residue of a partially damaged face-recognition network. Covert recognition may reflect the degree of damage across components of a network rather than mark a specific form of prosopagnosia or a dissociated pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 34 publications
5
60
1
Order By: Relevance
“…49,51 These include standard neuropsychological instruments such as the Warrington Recognition Memory test, 52 and the Benton Face Recognition test, 53 as well as our own experimental tests of discrimination of famous from anonymous faces, 54 and of facial imagery. 55 (In addition, the averaged upright configuration perception data from this report were also presented in one of these prior studies. 49 ) Cluster analysis confirmed at least two groups of subjects with SDD: one with normal face recognition (SDD-1) and one with abnormal face recognition (SDD-2).…”
Section: Discussionmentioning
confidence: 90%
“…49,51 These include standard neuropsychological instruments such as the Warrington Recognition Memory test, 52 and the Benton Face Recognition test, 53 as well as our own experimental tests of discrimination of famous from anonymous faces, 54 and of facial imagery. 55 (In addition, the averaged upright configuration perception data from this report were also presented in one of these prior studies. 49 ) Cluster analysis confirmed at least two groups of subjects with SDD: one with normal face recognition (SDD-1) and one with abnormal face recognition (SDD-2).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, the associative subtype of prosopagnosia (i.e., a deficit in recognizing various associations between facial identity and related attributes such as certain types of semantic information) is generally considered to be attributable to damages overriding the anterior temporal cortical areas (Damasio et al, 1982;De Renzi et al, 1991;Barton et al, 2002;Barton and Cherkasova, 2003). The APA task to which we subjected the monkeys in the present study was designed to functionally simulate semantic associations with facial identities, as such associations are apparently broken in patients with the associative subtype of prosopagnosia.…”
Section: Discussionmentioning
confidence: 99%
“…In the narrow sense, prosopagnosia indicates a cognitive inability to identify familiar individuals by their faces. Previous literature has suggested that there are two basic types of prosopagnosia (Damasio et al, 1982;De Renzi et al, 1991;Barton et al, 2002;Barton and Cherkasova, 2003). One of these two subtypes is apperceptive prosopagnosia, which implies a deficit in face recognition itself.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke patients are known to be left with prosopagnosia as residual deficit and specific localised lesions of these areas had been identified with this problem. 32,33 Balint's syndrome, a triad of simultagnosia, ocular apraxia and optic ataxia is described as a result of trauma, embolic stroke or even sub-acute HIV encephalitis. 34 Palinopsia (Perseveration of visual image even after the causative object is removed from the visual field otherwise described as 'persisting after-images') can result from right occipital damage due to stroke, trauma or tuberculoma.…”
Section: Discussionmentioning
confidence: 99%